Employer Branding and Compensation Effects on Job Seekers’ Interest in FMCG: Reputation as Mediator - Muhammad Arrazi Bagaswara; Arman Jaya; Hasanudin Hasanudin; Ikram Yakin (Pusat Riset dan Inovasi Nasional, 2025)
Today’s increasing number of companies in the Fast-Moving Consumer Goods (FMCG) sector is intensifying the competition among FMCG firms in Indonesia for top talent, which has triggered a “war for talent.” The battle to attract the best employees has become just as intense as the competition for customers, compelling organisations to distinguish themselves from their competitors to be seen as an appealing employer to prospective candidates and current staff. This study aims to identify the key factors that influence Employer Branding (EB) among job seekers in Indonesia to support FMCG companies in crafting more effective recruitment strategies. The research utilised a questionnaire survey with 250 respondents selected through quota sampling. Using Structural Equation Modelling (SEM) with the AMOS 23 tool, the results of this study indicate that company attractiveness, compensation, and company reputation can affect job application interest, where company attractiveness is the most influential factor in job application interest in FMCG companies. Company reputation has also been proven to mediate the influence of company attractiveness on job application desire.